Kerkdiensten in coronatijd: Een onderzoek naar de vormgeving en beleving van kerkdiensten in de eerste weken van de coronacrisis - Joosse, Mark; Schaeffer, Hans (Religie & Samenleving, 2021)
This article presents empirical research on how local protestant churches in the city of Utrecht organized their Sunday church services during the first weeks of the COVID-19 crisis in the Netherlands. After the first lockdown Sunday, on which many services were cancelled, most members took part in digital services of their own congregation on subsequent Sundays. Community with one another was missed most, while many still felt connected to God. Online services were considered a fine alternative, but also as one that cannot possibly replace meeting in real life. These findings arguably need theological reflection regarding the phenomenon of digital liturgical community formation. We reflect on the (dis)continuity between digital and o.ffline services as this relates to community formation, embodiedness, and the mediation of salvation. Concludingly, we point to three issues that may help local churches in drawing lessons from the COVID-19 pandemic regarding (digital) community formation.